Can Time-Lapse Incubation and Monitoring Be Beneficial to Assisted Reproduction Technology Outcomes? A Randomized Controlled Trial Using Day 3 Double Embryo Transfer - Guo, Yu-han; Liu, Yan; Qi, Lin; Song, Wen-yan; Jin, Hai-xia (Frontiers in Physiology, 2022)
Objective: To determine if the application of time-lapse incubation and monitoring can be beneficial to clinical outcomes in assisted reproductive technology. Methods: 600 patients were equally randomized to three groups: conventional embryo culture and standard morphological selection [CM group], time-lapse culture and standard morphological selection [TLM group], and time-lapse culture and morphokinetic selection [TLA group]. 424 undergoing fresh autologous in vitro fertilization cycles were analysized, 132 patients in the CM group, 158 in the TLM group, and 134 in the TLA group. Main outcomes included clinical outcomes, embryo development rates and perinatal outcomes. Results: Clinical pregnancy rates in the time-lapse groups were significantly higher than in the CM group (CM 65.2% vs. TLM 77.2% vs. TLA 81.3%). Implantation rates and live birth rates were significantly higher for the TLA group (59.7 % and 70.9 %) compared to the CM group (47.7% and 56.1%) but not compared to the TLM group (55.4 % and 67.1 %). There was no statistical difference in miscarriage and ectopic pregnancy rates among the three groups. Overall, birth-weight was significantly higher in the time-lapse groups (CM 2731.7g±644.8g vs. TLM 3066.5g±595.4g vs. TLA 2967.4g±590.0g). The birth-height of newborns in the TLM group was significantly longer than that of CM group and TLA group (CM 48.3cm±4.4cm vs. TLM 49.8cm±2.3cm vs. TLA 48.5cm±2.7cm). Conclusions: Time-lapse incubation and monitoring has a significant benefit on clinical pregnancy rates and on overall birth weights, while morphokinetic analysis is not necessary. Trial registration: ClinicalTrials.gov, NCT02974517. Registered 23 Novomber 2016, https://clinicaltrials.gov/ct2/show/NCT02974517?term=NCT02974517&draw=2&rank=1